Bridging Disclosure Gaps: The Role of Institutional Investors in Contingent Liabilities Reporting by Indian Listed Companies - Potharla, Srikanth (Copernican Journal of Finance & Accounting, 2025)
This study addresses an underexplored aspect of disclosure literature by examining how institutional investor heterogeneity – specifically foreign institutional investors (FII) and domestic institutional investors (DII) – influences contingent liabilities disclosure (CLD) in India. Drawing on agency, stakeholder, and resource dependence theories, this research analyzes how institutional investors reduce information asymmetry and enhance corporate transparency. Using data from 430 listed Indian firms spanning 5,483 firm-year observations (2006–2023), regression analysis is employed to assess the differential impacts of FII and DII on CLD, while controlling for firm-specific and sectoral variables. The results demonstrate that institutional ownership significantly enhances CLD, with FII exerting a notably stronger influence compared to DII. Larger firms exhibit higher disclosure levels due to increased scrutiny, whereas growth-oriented firms tend to limit disclosure strategically to protect competitive advantages. Sectoral analysis reveals stricter compliance in Basic Materials and Consumer Non-Cyclicals industries, with comparatively lower disclosure in the Financial and Technology sectors. The study contributes theoretically by highlighting institutional investors' multifaceted roles as governance agents, stakeholder representatives, and crucial capital providers. These findings offer timely insights for regulators and corporate leaders seeking to improve transparency standards and attract global investment through enhanced disclosure policies.